(untitled) (Journal of Universal Science Research, 2023)
Speech etiquette refers to the system of speech behavior, the rules of live conversation and correspondence, how to use the language and its tools in a specific situation and environment. English speech etiquette is a set of special words and expressions that give a polite form to English speech, as well as the rules according to which these words and expressions are used in practice in various communication situations. Speech etiquette imparts politeness to speech, regardless of its conten. You should greet your audience, introduce yourself, and state your topic and purpose. You should maintain eye contact, use gestures, and modulate your voice. You should avoid distractions, such as fidgeting, reading from notes, or checking your phone